Water Mills’ Role in Transformation of Valley-river Landscapes of the Right-Bank Ukraine - Lavryk, Oleksandr; Лаврик, Олександр; Лаврик, Александр (My University, 2018)
Based on the results of many years of research, the distribution of water mills in the middle part of the Dnieper and Southern Bug basins together with the watershed section within the highest elevations of the Pridneprovskii hill is analyzed. Water mills are considered as landscape-technical systems (LTS), which became the root cause of the transformation of modern valley-river landscapes of the Right Bank of Ukraine. On the basis of historical geographic analysis, the process of re-equipment and restructuring of water mills in a hydroelectric power plant is shown. In accordance with the degree of safety and technical status, eight categories of mill garden and landscape systems have been identified. The vast majority of the found mines are in the «destruction» stage. It is concluded that during the process of development of river valleys a certain algorithm is observed for water mills: engineering and technical building «water mill» (to the 10th century)  milled LTS (10th century – beginning of the 19th century)  milledhydroenergy LTS (19th century – mid-20th century)  hydropower LTS (from the middle of the 20th century). Ґрунтуючись на результатах багаторічних досліджень, проаналізовано поширення водяних млинів у середній частині басейнів Дніпра та Південного Бугу разом із смугою вододілу в межах найвищих висотних позначок Придніпровської височини. Водяні млини розглянуто як ландшафтно-технічні системи (ЛТчС), які стали першопричиною трансформації сучасних долинно-річкових ландшафтів Правобережної України. На основі історико-географічного аналізу показано процес переоблаштування й перебудови водяних млинів у гідроелектростанції. Відповідно до ступеня збереженості та технічного стану виокремлено вісім категорій млинарських ландшафтно-технічних систем. Переважна більшість виявлених млинів перебувають на стадії «руйнування». Зроблено висновок про те, що у процесі забудови річкових долин водяними млинами спостерігається певний алгоритм: інженерно-технічна споруда «водяний млин» (до X ст.)  млинарські ЛТчС (X ст. – початок XІX cт.)  млинарсько-гідроенергетичні ЛТчС (XІX cт. – середина ХХ ст.)  гідроенергетичні ЛТчС (з середини ХХ ст.). Врахування попереднього досвіду забудови річкових долин інженерно-технічними спорудами дає змогу конструктивно планувати використання природних ресурсів у їх межах.
Роль водяних млинів у трансформації долинно-річкових ландшафтів Правобережної України
Роль водяных мельниц в трансформации долинно-речных ландшафтов Правобережной Украины
Keywords: river valley; landscape; landscape-technical systems; water mills; hydroelectric power stations; річкова долина; ландшафт; ландшафтно-технічні системи; водяні млини; гідроелектростанції